2016
DOI: 10.1007/s40032-016-0312-3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of Static Tested Ramjet Dump Combustor

Abstract: The flow field of a Liquid Fuel Ram Jet engine side dump combustor with kerosene fuel is numerically simulated using commercial CFD code CFX-11. Reynolds Averaged 3-D Navier-Stokes equations are solved alongwith SST turbulence model. Single step infinitely fast reaction is assumed for kerosene combustion. The combustion efficiency is evaluated in terms of the unburnt kerosene vapour leaving the combustor. The comparison of measured pressures with computed values show that the computation underpredicts (*5 %) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To find out the accuracy and the range of applications, the software has been validated for various reacting flows pertaining to hydrogen and kerosene injection in the scramjet combustor including transverse H 2 injection in constant area duct [26], staged H 2 injection in from struts [27], pylon injectors [28], kerosene fuelled scramjet combustor with cavity injector [29] and ramp-cavity injector [30] All these simulations have revealed that although, there exists some differences near the injection zone, the computational and experimental value of the flow parameters in the diverging portion of the combustor (the major thrust providing element) match within 5%.…”
Section: The Solution Methodologymentioning
confidence: 99%
“…To find out the accuracy and the range of applications, the software has been validated for various reacting flows pertaining to hydrogen and kerosene injection in the scramjet combustor including transverse H 2 injection in constant area duct [26], staged H 2 injection in from struts [27], pylon injectors [28], kerosene fuelled scramjet combustor with cavity injector [29] and ramp-cavity injector [30] All these simulations have revealed that although, there exists some differences near the injection zone, the computational and experimental value of the flow parameters in the diverging portion of the combustor (the major thrust providing element) match within 5%.…”
Section: The Solution Methodologymentioning
confidence: 99%
“…Various injection strategies including wall injection [5,6,7,8], ramp cavity [9,10], strut [11,12], pylons [13] etc. were tried for both hydrocarbon and hydrogen fuelled scramjet combustor.…”
Section: Introductionmentioning
confidence: 99%
“…Also, due to the occurring of reaction close to the surface, combustor walls experience excessive thermal loads and the walls are made FULL LENGTH PAPER thicker to withstand the high thermal load. The problem of lateral fuel transport in the air stream can be circumvented by injecting the fuel in the core region of the flow by means of struts [11,12] and or pylons [13]. The oblique shocks generated from the struts also augment the mixing which is very much needed in high speed propulsion devices.…”
Section: Introductionmentioning
confidence: 99%